A Granger causality analysis between stock prices and exchange rates: evidence from four countries. (8th June 2023) - Phoong, Seuk Yen; Lim, Cheng Zhi; Phoong, Seuk Wai
This study investigates predictive causality between stock prices and exchange rates over the period of January 2005 to May 2020 in Malaysia, Singapore, China, and USA. The methodology applied in this study allows for structural changes during the global financial crisis, as past studies have shown that tests can be biased towards non-rejection if structural breaks are not accounted for. Thence, Gregory and Hansen cointegration and Granger causality tests are implemented in this study. Results revealed that unidirectional Granger causality relations are established in Malaysia, the US, and Singapore. However, signs for causal effects differ even though two markets have the same unidirectional Granger causality relation. Additionally, stock prices and exchange rates are found to be cointegrated in the US and Singapore. Meanwhile, there is no causal effect between stock prices and the exchange rate in China, for both the short-run and long-run periods.